PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION UNTUK MENINGKATKAN HASIL BELAJAR AL-QURAN HADIS - Bubun Sihabul Millah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
The aims of this research is to obtain an overview about student learning outcomes in the application of the Cooperative Learning model, CIRC (Cooperative Integrated Reading and Composition) Type on the subject of Al-Qur’an Hadith. The type of this research is classroom action research which was carried out in three cycles, each meeting consist of some stages; planning, action, observation, and reflection. The subject of this research was 30 student of the XII IPS 2 grade of MAN Cililin West Bandung. The data which is obtained in this research are include: learning outcomes and student learning completeness which taken from the test giving at the end of each meeting and the students activity in the learning process. The result of the research data after using Cooperative learning model, CIRC (Cooperative Integrated Reading and Composition) type at first till the end cycles showed an increasing students learning outcomes. Thus it can be conclude that using cooperative learning model, CIRC (Cooperative Integrated Reading and Composition) type can increase students learning outcomes.